2012
DOI: 10.1371/journal.pntd.0001789
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Peripheral T Cells and Their Dynamics in Scrub Typhus Patients

Abstract: BackgroundScrub typhus, caused by Orientia tsutsugamushi infection, is one of the main causes of febrile illness in the Asia-Pacific region. Although cell-mediated immunity plays an important role in protection, little is known about the phenotypic changes and dynamics of leukocytes in scrub typhus patients.Methodology/Principal FindingsTo reveal the underlying mechanisms of immunological pathogenesis, we extensively analyzed peripheral blood leukocytes, especially T cells, during acute and convalescent phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 55 publications
2
41
0
1
Order By: Relevance
“…Although the cytokine responses in IFNAR KO mice were similar to wild type, the level of IFN-ฮณ was further elevated upon infection with O. tsutsugamushi , suggesting enhanced Th1 responses in the absence of type I IFN signaling. This phenotype was confirmed by a significant increase of T-bet + CD44 + Th1 cell proportion, as well as IFN-ฮณ-secreting activated CD4 T cells, among CD4 T cell population in IFNAR KO mice; however, the levels of CD4 T cell subsets were similarly decreased in both wild type and the mutant mice, potentially via cellular apoptosis, as we observed in scrub typhus patients previously (Figures 4B,C and Table S2 ) ( 20 ). The initial increase of antigen-specific Th1 responses were correlated with significant enhancement of memory T cells, and functionally associated with improved sterile immunity upon secondary bacterial challenge in IFNAR KO mice (Figure 5 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the cytokine responses in IFNAR KO mice were similar to wild type, the level of IFN-ฮณ was further elevated upon infection with O. tsutsugamushi , suggesting enhanced Th1 responses in the absence of type I IFN signaling. This phenotype was confirmed by a significant increase of T-bet + CD44 + Th1 cell proportion, as well as IFN-ฮณ-secreting activated CD4 T cells, among CD4 T cell population in IFNAR KO mice; however, the levels of CD4 T cell subsets were similarly decreased in both wild type and the mutant mice, potentially via cellular apoptosis, as we observed in scrub typhus patients previously (Figures 4B,C and Table S2 ) ( 20 ). The initial increase of antigen-specific Th1 responses were correlated with significant enhancement of memory T cells, and functionally associated with improved sterile immunity upon secondary bacterial challenge in IFNAR KO mice (Figure 5 ).…”
Section: Discussionsupporting
confidence: 87%
“…The intracellular pathogen has tropism for dendritic cells, monocytes/macrophages, and endothelial cells ( 10 ), where it replicates in the cytosol and induces multiple inflammatory mediators. Additionally, systemic O. tsutsugamushi infection in humans causes neutrophilia and CD4 T lymphopenia in the acute phase, followed by proliferation of CD8 T cells with activated phenotype during convalescent phase ( 20 ). Such potent immuno-pathological changes in innate and adaptive immune system might be associated with clinical presentations of scrub typhus such as eschar, fever, rash, lymphadenopathy, systemic vasculitis, and multi-organ failure often observed in fatal cases.…”
Section: Introductionmentioning
confidence: 99%
“…Giamarellos-Bourboulis et al have reported increased circulating NK cell levels in Gram-negative severe sepsis in humans [ 35 ], whereas others have reported a decline in NK cells in severe sepsis or septic shock [ 36 , 37 , 38 ]. Interestingly, only one study reported no evidence of change in the frequency of total NK cells in scrub typhus patients [ 39 ]. These discrepant findings about circulating NK cell levels might be due to the differences in pathogen, severity, time point at which the sample was obtained, and cohort selection bias including age and sex studied.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 And, scrub typhus causes profound disturbances in T cell homeostasis. 20 This opens the possibility that mechanisms other than antibiotic resistance/failure are causes of meningeal presentations.…”
Section: Discussionmentioning
confidence: 99%